Hydroponic Farming: A Strategy For Food Strategy at The Household Scale in Lubuk Minturun, Koto Tangah Sub-District, Padang - Mariya, Sri; Wilis, Ratna; Wijayanto, Bayu; Syarief, Azhari (Sumatra Journal of Disaster, Geography and Geography Education, 2025)
The low consumption of vegetables is the main cause of health problems ranging from obesity, cancer, stroke, chronic kidney disease, diabetes mellitus to hypertension. The consumption of vegetables and fruits by the Indonesian population is still below the recommended levels. Lubuk Minturun Village is one of the areas with an increasing population every year, with residential areas surrounding the vicinity. The high demand for horticultural plants among the community has led to the idea of ​​utilizing the household environment to cultivate horticultural plants to meet daily needs. One effort that can be made is by using hydroponic systems, so that both the community and housewives do not need to have large plots of land to cultivate horticultural plants; instead, they can utilize the environment or the yard of the house to cultivate these plants. Several approaches offered to support the realization of this community service program include training and demonstrations, including: (1) Case Studies, (2) Practice/demonstration, especially in hydroponic cultivation, (3) Brainstorming/idea gathering from the community, (4) Question and answer sessions between housewives and speakers or relevant government agencies, (5) Lectures containing core materials and plans for further activities that provide solutions to the problems faced by housewives. This activity is very beneficial and has resulted in: (1) Increased knowledge of housewives in utilizing yards with hydroponic systems, (2) Increased knowledge and skills of housewives in utilizing recycled materials as media for hydroponic cultivation, (3) Increased knowledge and skills of housewives in hydroponic cultivation and maintenance.